2006
DOI: 10.1007/s00535-005-1748-z
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive rectal painful distention induces rectal hypersensitivity in patients with irritable bowel syndrome

Abstract: Rectal hypersensitivity induced by RRD may be a reliable marker for IBS. Conditioning-induced visceral hypersensitivity may play a pathophysiologic role in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 21 publications
2
20
0
2
Order By: Relevance
“…18 Since RRD in the present study is also a visceral stimulation, RRD may stimulate CRF release. On the other hand, the present study also revealed that RRD without iv-CRF did not alter rectal sensation, which is consistent with our previous report, 7 and, moreover, iv-CRF alone did not induce it either, suggesting that both exogenous (iv) and endogenously released CRF in the brain induced by RRD may be required to achieve rectal hypersensitivity. Because of the bloodbrain barrier, iv-CRF does not penetrate to the brain.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…18 Since RRD in the present study is also a visceral stimulation, RRD may stimulate CRF release. On the other hand, the present study also revealed that RRD without iv-CRF did not alter rectal sensation, which is consistent with our previous report, 7 and, moreover, iv-CRF alone did not induce it either, suggesting that both exogenous (iv) and endogenously released CRF in the brain induced by RRD may be required to achieve rectal hypersensitivity. Because of the bloodbrain barrier, iv-CRF does not penetrate to the brain.…”
Section: Discussionsupporting
confidence: 94%
“…7 In our present study, we also showed that PT in the basal state was 32-35 mmHg (n = 21, all men), and recently another preliminary Japanese study reported that PT of healthy male subjects (n = 6) is around 32 mmHg. 15 Since these values are quite comparable, the reproducibility of PT between different Japanese subjects and laboratories seems to be quite good, indicating that these values can be considered reliable.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This selective hypersensitization occurs as a result of stimulation of various receptors of visceral afferent nerve fibres in the gut wall, triggered by bowel distention or bloating, and is a possible explanation for IBS symptoms. The increased sensitivity of the colon could be influenced by a psychological tendency to report pain and urgency, rather than increased neurosensory sensitivity 26,27 .…”
Section: Intestinal Hypersensitivitymentioning
confidence: 99%